PERHITUNGAN PERFORMA ALAT PENUKAR KALOR TIPE PELAT SH1 54-M10-50 TERHADAP VARIASI JUMLAH PELAT PADA PROSES RECOVERY CS2 di PT ASIA PACIFIC RAYON - Allo, Sipry T.; Luntungan, Hengky; Maluegha, Benny L. (Jurnal Tekno Mesin, 2024)
Plate-type heat exchangers in the process industry are generally used for efficient heat transfer between two fluid streams. The number of plates used affects the performance of the heat exchanger. This study aims to determine the performance of the SH1 54-M10-50 plate type heat exchanger against the variation in the number of plates being used in the CS2 recovery process and the performance at the number of calculated plates and determine the effective number of plates in the plate type heat exchanger for the CS2 recovery process based on performance calculations and simulations. The research was conducted at PT Asia Pacific Rayon in Pangkalan Kerinci, Riau and the CAD-CAM Lab of the mechanical engineering department, Sam Ratulangi University Manado, from February to April 2024. The performance of the heat exchanger was determined by calculation and simulation. Simulation of plate-type heat exchanger performance using Solidworks software. The results show that with 40 plates, the hot fluid exit temperature is 69.31°C and the cold fluid exit temperature is 67.4°C, with a total pressure of 4.48 bar and 4.76 bar, respectively. The calculation results are similar to the simulation results with the largest difference being 2.6%. For 50 plates, the temperatures are 65.92°C and 58.55°C, with total pressures of 4.34 bar and 4.57 bar, respectively. Based on calculations and simulations on the variation in the number of plates carried out, it shows that the effective variation in the number of plates for the CS2 recovery process between the 40 plate variation and the 50 plate variation is the 40 plate variation. Keywords: plate heat exchanger, performance, software. ABSTRAK Penukar kalor tipe pelat dalam industri proses umumnya digunakan untuk perpindahan kalor yang efisien antara dua aliran fluida. Jumlah pelat yang digunakan mempengaruhi kinerja penukar kalor. Penelitian ini bertujuan untuk mengetahui performa penukar kalor tipe pelat SH1 54-M10-50 terhadap variasi jumlah pelat yang sedang digunakan pada proses recoveri CS2 dan performa pada jumlah pelat hasil perhitung serta menentukan jumlah pelat yang efektif pada penukar kalor tipe pelat untuk proses recovery CS2 berdasarkan perhitungan kinerja dan simulasi. Penelitian dilakukan di PT Asia Pacific Rayon di Pangkalan Kerinci, Riau dan Lab CAD-CAM juruasan teknik mesin, Universitas Sam Ratulangi Manado, pada bulan Februari hingga April 2024. Performa alat penukar kalor ditentukan dengan perhitungan dan simulasi. Simulasi kinerja penukar kalor tipe pelat menggunakan perangkat lunak Solidworks. Hasil penelitian menunjukkan bahwa dengan 40 pelat, temperatur keluar fluida panas sebesar 69,31°C dan temperatur keluar fluida dingin sebesar 67,4°C, dengan tekanan total masing-masing sebesar 4,48 bar dan 4,76 bar, pada perhitungan hasil adalah mirip dengan hasil simulasi dengan selisih terbesar adalah 2,6 % . Untuk 50 pelat, temperaturnya 65,92°C dan 58,55°C, dengan tekanan total masing-masing 4,34 bar dan 4,57 bar. Berdasarkan perhitungan dan simulasi pada variasi jumlah pelat yang dilakukan menunjukkan bahwa variasi jumlah pelat yang efektif untuk proses recovery CS2 antara variasi 40 pelat dan variasi 50 pelat adalah pada variasi 40 pelat. Kata kunci: penukar kalor tipe pelat, performa, perangkat lunak.